Perpustakaan Sebagai Literasi Informasi Bagi Pemustaka - Mulyadi Mulyadi (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: As a result of the continued development of information and communication technology , millions of information has spread everywhere . Especially at this time in the library as a means of support information literacy , there are many sources of media that we can access . For example : library in addition to providing print media such as books , journals , magazines , newspapers , also provide nonprinting media such as radio , television , the Internet and various other forms of multimedia types . Information literacy is a skill when information is needed , in order to find the right information , and skills in analyzing and utilizing relevant information . librarian  will teach information literacy to explore information independently from various information sources are found , as well as resources that exist today are constantly evolving . With the information literacy , librarian be able to process information correctly . These skills who will be able to support the needs librarian in teaching and learning . It can be concluded that the library and information literacy are two things related to each other . Literacy information will not be complete without the presence of an adequate library . Keywords : Literacy , Information , Information Literacy , Library .